Loading Gentamicin and Zn2+ on TiO2 Nanotubes to Improve Anticoagulation, Endothelial Cell Growth, and Antibacterial Activities. (4th May 2021) - Lin, Yuebin; Zhang, Li; Yang, Ya; Yang, Minhui; Hong, Qingxiang; Chang, Keming; Dai, Juan; Chen, Lu; Pan, Changjiang; Hu, Youdong; Quan, Li; Wei, Yanchun; et al.
Abstract : Titanium and its alloys are widely used in blood-contacting implantable and interventional medical devices; however, their biocompatibility is still facing great challenges. In the present study, in order to improve the biocompatibility and antibacterial activities of titanium, TiO2 nanotubes were firstly in situ prepared on the titanium surface by anodization, followed by the introduction of polyacrylic acid (PAA) and gentamicin (GS) on the nanotube surface by layer-by-layer assembly, and finally, zinc ions were loaded on the surface to further improve the bioactivities. The nanotubes displayed excellent hydrophilicity and special nanotube-like structure, which can selectively promote the albumin adsorption, enhance the blood compatibility, and promote the growth of endothelial cells to some degree. After the introduction of PAA and GS, although the superhydrophilicity cannot be achieved, the results of platelet adhesion, cyclic guanosine monophosphate (cGMP) activity, hemolysis rate, and activated partial thromboplastin time (APTT) showed that the blood compatibility was improved, and the blood compatibility was further enhanced after zinc ion loading. On the other hand, the modified surface showed good cytocompatibility to endothelial cells. The introduction of PAA and zinc ions not only promoted the adhesion and proliferation of endothelial cells but also upregulated expression of vascular endothelial growth factor (VEGF) and nitric oxide (NO). The slow and continuous release of GS and Zn 2+ over 14 days can significantly improve the antibacterial properties. Therefore, the present study provides an effective method for the surface modification of titanium-based blood-contacting materials to simultaneously endow with good blood compatibility, endothelial growth behaviors, and antibacterial properties.